2004
DOI: 10.1007/s10194-004-0100-3
|View full text |Cite
|
Sign up to set email alerts
|

A one-year prospective costing study of botulinum toxin type A treatment of chronic tension headache

Abstract: The objective was to measure the cost of botulinum toxin type A (BTX-A) treatment of chronic tension-type headache. A prospective pharmaceutical costing analysis was completed in the Day Hospital of the Regional Referral Headache Centre at Sant'Andrea Hospital in Rome, chronic tension-type headache patients were treated from February 2003 to January 2004. Patients were treated with 100 U of BTX-A every three months for one year by using the Fixed Doses Fixed Sites procedure. The cost of treatment was based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Using the other predefined exclusion criteria, we were left with 43 studies of which we reviewed the full text. Three were excluded due to being case series or a cost‐effectiveness study, or lacking differentiation between migraine and TTH when discussing patients with chronic daily headache in their cohort . The other excluded studies did not meet inclusion criteria as noted above.…”
Section: Resultsmentioning
confidence: 99%
“…Using the other predefined exclusion criteria, we were left with 43 studies of which we reviewed the full text. Three were excluded due to being case series or a cost‐effectiveness study, or lacking differentiation between migraine and TTH when discussing patients with chronic daily headache in their cohort . The other excluded studies did not meet inclusion criteria as noted above.…”
Section: Resultsmentioning
confidence: 99%
“…One year of in-hospital BoNT-A therapy amounts to €564.00 including pharmaceutical costs, consumable supplies and personnel. The total cost of BoNT-A treatment per patient was €642.00, whilst average costs of previous therapies amounted to €853.43 [41,42]. This can be considered together with a reduction of clinic symptomatology and analgesic intake [43].…”
Section: Five-year Experience With Bont-a In Cdhmentioning
confidence: 99%
“…A subsequent one-year prospective analysis revealed that after BoNTA treatment there was a 45% reduction in the consumption of analgesics/antimigraine drugs, a 35% reduction of NSAIDs and a 100% reduction of other off-label prophylactic agents. The average costs of medications had been reduced from € 853.43 before BoNTA treatment to € 450.47 afterwards [16]. The overall conclusion of these studies displayed, together with BoNTA's efficacy for CTH, a substantial reduction of headache medication utilisation and costs.…”
mentioning
confidence: 87%